Teaching essential literacy skills in the early years classroom a guide for students and teachers - Concannon-Gibney, Tara (Routledge, 2019)
"Teaching and learning literacy in the early years can be a joyful, explorative and meaningful experience. This accessible book will give teachers and practitioners the practical and theoretical skills and knowledge they require to successfully and confidently teach reading, writing and oral skills in the early years classroom. Foregrounding the ways in which literacy instruction can be made enjoyable and meaningful from the very beginning, Teaching Essential Literacy Skills in the Early Years Classroom explores the theory and practice of teaching various aspects of literacy and language; from phonological awareness, phonics, and fluency, to vocabulary and comprehension. Chapters draw on the latest research to identify and showcase best practice in writing instruction, illustrate how language and literacy can be developed through play, and outline how a teacher might use the environment to enhance children's learning. Downloadable resources, examples of planning, classroom activities and vignettes can be quickly and easily adapted for use in any early years setting. A rich and comprehensive source of information, ideas, activities and tips, this will be a key resource for pre- and in-service teachers and practitioners looking to adopt a cohesive, effective and meaningful approach to literacy teaching and learning"--